2009
DOI: 10.1021/jp9032904
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Rare-Earth Doped Yttrium Aluminoborate Laser Glasses Using Solid State NMR

Abstract: The structure of laser glasses in the system (B 2 O 3 ) 0.6 {(Al 2 O 3 ) 0.4-x (Y 2 O 3 ) x } (0.1 e x e 0.25) has been investigated by means of 11 B, 27 Al, and 89 Y solid state NMR as well as Y-3d core-level X-ray photoelectron spectroscopy. 11B magic-angle spinning (MAS) NMR spectra reveal that the majority of the boron atoms are three-coordinated, and a slight increase of four-coordinated boron content with increasing x can be noticed. 27 Al MAS NMR spectra show that the alumina species are present in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 55 publications
5
58
0
1
Order By: Relevance
“…In the glassy state, the dominant fraction of boron is three-coordinated, giving rise to a broad structured lineshape characterized by second-order quadrupolar perturbations. As previously discussed, the lineshape suggests a non-axially symmetric electric field gradient, consistent with the formation of mostly metaborate (three-coordinate boron with one non-bridging oxygen) and pyroborate (three-coordinate boron with two non-bridging oxygen) groups [20]. The chemical shift difference between the latter two units appears to be obscured by a wide distribution of quadrupolar coupling parameters and chemical shifts.…”
Section: Xrd Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…In the glassy state, the dominant fraction of boron is three-coordinated, giving rise to a broad structured lineshape characterized by second-order quadrupolar perturbations. As previously discussed, the lineshape suggests a non-axially symmetric electric field gradient, consistent with the formation of mostly metaborate (three-coordinate boron with one non-bridging oxygen) and pyroborate (three-coordinate boron with two non-bridging oxygen) groups [20]. The chemical shift difference between the latter two units appears to be obscured by a wide distribution of quadrupolar coupling parameters and chemical shifts.…”
Section: Xrd Resultssupporting
confidence: 79%
“…40), containing Yb at variable dopant levels were prepared as described previously [6,20], by the conventional melt-quenching technique, using a resistive furnace open to the atmosphere. To obtain a water free starting material, glassy boron oxide was prepared by annealing commercial B 2 O 3 (ALDRICH, 99%) at 450 1C for 2 h, with a heating rate of 5 1C/min, for the evaporation of water.…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…While continuing our systematic exploration of 45 Sc NMR interaction parameters in relation to the local environments and electronic structures of ternary Sc x T y X z (T¼ transition metal; X¼element of the 3rd, 4th, and 5th main group) intermetallic compounds [6] we are now also pursuing parallel 89 Y investigations on structurally related yttrium compounds. While highresolution solid state 89 Y NMR spectroscopy of diamagnetic insulators has been well-developed by now [7][8][9][10][11][12][13][14], NMR applications to metallic systems have thus far been limited mostly to low-resolution work on the electronic and magnetic properties of yttrium hydrides [15][16][17][18][19], yttrium-iron based alloys [20][21][22] and borocarbides [23]. The only structurally focused high-resolution Mössbauer spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported on the luminescence and thermo-optical properties of Nd 3+ -doped YAl 3 (BO 3 ) 4 (YAlB) glasses with higher fluorescence quantum efficiency than the Nd:YAB crystal, 9 and on a detailed structural investigation of the glasses, and their corresponding vitroceramics, as a function of compositional changes. 11,12 However, to the best of our knowledge, there have been no reports on the spectroscopic and thermo-optical characterization of undoped and Nd 3+ -doped YCa 4 O(BO 3 ) 3 (YCaB) glasses, which have been recently introduced by some of us. 10,19 A structural study of samples with compositions xY 2 O 3-8xCaO-(100−9x)B 2 O 3 (x = 4, 5, and 6 mol%), via Raman and infrared reflectance spectroscopies, has shown that the glasses contain a complex distribution of three-coordinated ortho and pyroborate groups and four-coordinated pentaborate groups, and as the CaO a) Electronic mail: andreasc@ifsc.usp.br.…”
mentioning
confidence: 99%